Mechanization, Automation, Robotization and Digitalization: Conceptual Clarification and Systematization - V. M. Korotchenya (Сельскохозяйственные машины и технологии)
The paper highlights the importance of clarifying scientific terminology to delineate the exclusion of humans from technical systems, in particular the concepts such as «mechanization,» «automation,» «robotization,» and «digitalization» that are commonly used in scientific literature without a precise definition of their essence and distinctions. (Research purpose) The paper aims to provide clarity and systematic categorization of terms employed to describe the exclusion of humans from agricultural technical systems. (Materials and methods) The paper employs the Theory of Inventive Problem Solving (TRIZ), the Theory of Decision Making, and the System Method as theoretical frameworks. (Results and discussion) The paper provides a comprehensive clarification of the conceptual meanings attributed to terms such as mechanization, automation, robotization, and digitalization. It outlines their classical (Aristotelian) definitions and systematically categorizes a broad spectrum of related concepts, including mechanization, automation, robotization, intellectualization, digitalization, cyber-physical system, precision agriculture, digital agriculture, and smart (intelligent) agriculture. The obtained results are compared utilizing the approach of the Food and Agriculture Organization of the United Nations (FAO). (Conclusions) It is concluded that the concept of mechanization, in contrast to the FAO approach, does not encompass farming reliant on manual labor and animal traction. It is determined that robotization necessitates intellectualization, whereas automation does not necessarily require it. Furthermore, digitalization is demonstrated as a means of implementing automation, robotization, intellectualization, and optimizing the operation of technical systems.